Propuesta de un plan estratégico para la empresa ¨Carpintería de Casas Enríquez¨ de la ciudad de Cuenca; periodo 2015 - 2019 - Maldonado Rojas, Diana Yuri (2015)
Economic and political instability that our country has suffered for many years has caused the closure of many companies thus affecting the forestry sector due to the high cost of taxes, among others that do not allow improve services. This project's general objective is the development of a Strategic Plan for the Carpinteria Enriquez Houses Cuenca Company; Period 2015 - 2019, the same that would promote the development and growth of the company, which has been made based on theoretical underpinnings and field information obtained through the use of surveys and interviews with 120 clients, 9 employees and their manager. In terms of methodology, it is part of making a situational analysis of the company, by applying the manager surveys and interviews, employees and business users. With internal and external analysis SWOT matrix that allowed me to define the opportunities, threats, strengths and weaknesses, so that the array of high impact with what we proceeded to perform the FO, DO, FA combination was built was built, DA resulting in the strategic objectives. Within the weighted results of the evaluation matrix EFI internal factors could be determined which has a weighting of 2.47 which means that there are problems Strengths - Weaknesses. While EFE matrix has a weighting of 2.41 which implies that the company has an internal potential which can confront the threats and seize opportunities. Finally PROPOSAL OF A STRATEGIC PLAN FOR THE HOUSE CARPINTERIA Enriquez de Cuenca was developed; PERIOD 2015 - 2019. Recommending the implementation of it, as it will help the company capture new customers, increase sales and generate higher returns